Scoping Review About Salmonella spp. in Colombian Pig Farms from 2009 to Mid-2024 - Adriana Pulido-Villamarín; Iliana Chamorro-Tobar; Ana K. Carrascal-Camacho; Fernando Sampedro; Marcela Rodríguez-Moreno; Fernando Rojas-Bermúdez; Mónica Pérez-Vargas; Ivonne Hernández-Toro; Alejandra Camacho-Carrillo; Raúl A. Poutou-Piñales (Animals)
In Colombia, research on Salmonella concerning animal health, veterinary diagnostics, and epidemiology within the primary production chain is limited. This study aimed to analyze the published data about Salmonella in the Colombian primary pig production chain from 2009 to mid-2024. This involved an exploratory literature review using systematic search strategies, including articles, graduate studies, conference presentations, and technical reports from the selected period. Of the 35 studies reviewed, 30 met the inclusion criteria, with eleven being from the grey literature. The pooled prevalence of Salmonella spp. on Colombian farms was 8.9%, while the seroprevalence ranged from 27 to 40%. Risk factors associated with the presence of this bacterium on farms included aspects such as water sources, pest control, the farm type, and management practices. Few scientific publications address the presence of this pathogen in primary pig production in Colombia, underscoring the need to raise awareness within the academic and production communities about the importance of conducting and reporting new studies and cases.